KumahAbi method in the inquiry model: Improved concept understanding in multiplication materials - Pratama, Ramadhany Adam; Puspita, Hany Dwi; Hoor, Adriana R. Elsa; Abdurrazzaq, Achmad (Desimal: Jurnal Matematika, 2023)
Mathematics is a subject studied from elementary school to university level. At the elementary school level, mathematics learning aims to provide students with an understanding of the concept of numbers. There are four basic arithmetic operations that must be mastered by primary school students, namely addition, subtraction, multiplication, and division. The concept of multiplication has a higher level of difficulty than addition or subtraction, so students need more time to master this concept. Learning methods applied in the classroom are important in encouraging students to understand learning. Conventional learning methods force students to memorize multiplication concepts, so students only memorize and do not understand basic concepts. Therefore, we need a learning method that can stimulate students' logical thinking and creativity in solving multiplication problems systematically. In this research, a new learning method was introduced by combining the inquiry learning model called the KumahAbi method. The results of this study show that the implementation of the KumahAbi method in learning is very effective in improving students' understanding of multiplication.